Acquired Resilience: An Evolved System of Tissue Protection in Mammals - Jonathan Stone; John Mitrofanis; Daniel M. Johnstone; Benedetto Falsini; Silvia Bisti; Paul Adam; Arturo Bravo Nuevo; Mindy George-Weinstein; Rebecca Mason; Janis Eells (SAGE Publishing, 2018)
This review brings together observations on the stress-induced regulation of resilience mechanisms in body tissues. It is argued that the stresses that induce tissue resilience in mammals arise from everyday sources: sunlight, food, lack of food, hypoxia and physical stresses. At low levels, these stresses induce an organised protective response in probably all tissues; and, at some higher level, cause tissue destruction. This pattern of response to stress is well known to toxicologists, who have termed it hormesis. The phenotypes of resilience are diverse and reports of stress-induced resilience are to be found in journals of neuroscience, sports medicine, cancer, healthy ageing, dementia, parkinsonism, ophthalmology and more. This diversity makes the proposing of a general concept of induced resilience a significant task, which this review attempts. We suggest that a system of stress-induced tissue resilience has evolved to enhance the survival of animals. By analogy with acquired immunity, we term this system 'acquired resilience'. Evidence is reviewed that acquired resilience, like acquired immunity, fades with age. This fading is, we suggest, a major component of ageing. Understanding of acquired resilience may, we argue, open pathways for the maintenance of good health in the later decades of human life.